The Mediating Role of Brand Image in the Relationships between Interactivity, Electronic Word of Mouth (E-WOM), and Purchase Intention among Generation Z - Kadek Masakazu; I Gusti Ngurah Satria Wijaya; Gede Suwardika; I Ketut Putu Suniantara (Bina Nusantara University, 2025)
The world is still evolving, and in this era of disruption, everything is based on digital technology. A new phenomenon has emerged in the business world in recent years, namely the bankruptcy of a number of large companies in Indonesia like Giant and the closure of several Carrefour outlets and Matahari Department Store. The research aimed to analyze the effect of interactivity and Electronic Word of Mouth (E-WOM) on the intention to purchase Erigo products with the brand image as a mediating variable on Generation Z in Denpasar City. As the respondents, 208 samples from Denpasar City’s Generation Z population were selected using a purposive selection technique. The analysis method used was Structural Equation Modeling (SEM) through Partial Least Squares (PLS-SEM). As a result, Generation Z in Denpasar City is positively and significantly influenced by brand image, E-WOM, and interactivity when it comes to their intention to buy Erigo fashion items. When it comes to the purchase intention for Erigo products, brand image has the ability to mediate the impact of TikTok interactivity and E-WOM. The managerial implications include the need for Erigo management to focus on the factors influencing potential customers’ decisions to purchase Erigo products, specifically interactivity, E-WOM, and brand image.